Cyber Public Relations Strategy of SMAN 9 Tangerang Regency in Building Shared Value - Rauf, Abdul; Prihantoro, Edi (Green Publisher Indonesia, 2026)
The Cyber Public Relations (PR) strategy at SMAN 9 Kabupaten Tangerang aims to build better relationships with the community through the use of social media and digital platforms. This study analyzes SMAN 9’s efforts in creating shared value by utilizing digital communication technology as a tool to strengthen both internal and external communication. The focus of the research is on how SMAN 9 leverages digital platforms such as Instagram, Facebook, YouTube, and WhatsApp to deliver educational content, build audience engagement, and enhance transparency and accountability. The findings show that the use of this Cyber PR strategy has successfully strengthened relationships with students, parents, alumni, and the surrounding community, creating shared value that benefits all parties. However, challenges related to human resource and budget management remain a major obstacle that needs to be addressed to optimize this strategy.